Konsep Pendidikan Karakter Toleransi Untuk Membangun Persaudaraan Perspektif Quraish Shihab dalam Tafsir Al-Mishbah: The Concept of Tolerance Character Education for Building Brotherhood: Quraish Shihab’s Perspective in Tafsir Al-Mishbah - Iman, Nuril; Mochamad Nurcholiq; A. Qomarudin (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2025)
Indonesia is a nation rich in cultural, ethnic, and religious diversity. However, this diversity also poses challenges to social harmony, as it can sometimes trigger conflicts, particularly those related to religion. In this context, character education for tolerance is a vital collective endeavour. M. Quraish Shihab offers a profound perspective on tolerance education in Islam through his Tafsir Al‑Mishbah. This study analyzes Shihab’s concepts of building brotherhood and of forming a tolerant character as presented in Tafsir Al‑Mishbah. Employing a qualitative library‑research approach, the study collects, reviews, and analyzes primary, secondary, and tertiary literature relevant to the topic. The findings indicate that Shihab’s concept of character education for tolerance is grounded in the principle of ukhuwah (brotherhood), which encompasses religious, national, and humanitarian dimensions. He advocates contextual, moderate, and humanistic approaches that promote inclusivity and respect for diversity. The study suggests that Qurʾanic‑based character education for tolerance should be integrated into Islamic education curricula to cultivate individuals who are tolerant, just, and capable of living peacefully in plural societies.